Neuroprem 2: An Italian Study of Neurodevelopmental Outcomes of Very Low Birth Weight Infants - Lugli, Licia; Bedetti, Luca; Guidotti, Isotta; Pugliese, Marisa; Picciolini, Odoardo; Roversi, Maria Federica; DellaCasa Muttini, Elisa; Lucaccioni, Laura; Bertoncelli, Natascia; Ancora, Gina; Gargano, Giancarlo; Mosca, Fabio; et al. (Frontiers in Pediatrics, 2021)
Background: Despite the increased survival of preterm newborns worldwide, the risk of neurodevelopmental disabilities remains high. Analyzing the outcomes of the preterm population can identify risk factors and enable specific early interventions. Aims: Neuroprem is a prospective cohort study of very low birth weight (VLBW) infants that aims to evaluate the neurodevelopmental outcomes and risk factors for severe functional disability at 2 years of corrected age. Methods: Nine Italian neonatal intensive care units participated in the network. The Griffiths Mental Developmental Scales (GMDS-R) or the Bayley Scales of Infant and Toddler Development (BSDI III) and a neuro-functional evaluation (according to the International Classification of Disability and Health and Neuro-Functional Assessment, or NFA ICF-CY) were administered to VLBW infants at 24 months of corrected age. The primary outcome measure was severe functional disability, defined as cerebral palsy, bilateral blindness, deafness, an NFA ICF-CY of >2, a BSDI III cognitive composite score of <2 SD, or a GMDS-R global quotient score of <2 SD. Perinatal risk factors for severe functional disability were assessed through multivariate logistic regression analysis. Results: Among 502 VLBW survivors who completed the 24-month follow-up, 48 (9.6%) presented severe functional disability, of whom 27 had cerebral palsy (5.4%). Rates of severe functional disability and cerebral palsy were higher in neonates with a lower gestational age (p<.001). Overall, 147 infants (29.3%) were referred to neuromotor intervention. In the multivariate regression model, gestational age at birth (OR 0.79; 95% CI 0.67–0.90; p=.001) and periventricular-intraventricular hemorrhage (OR 2.51; 95% CI 1.19–5.26; p=.015) were significantly associated with severe functional disability. Conclusion: Neuroprem 2 provides updated information on the neurodevelopmental outcomes of VLBW infants in a large Italian cohort. The overall rate of neurodevelopmental disabilities was quite lower than reported in the previous literature. These data indicate the need for structured follow-up programs from a national neonatal network perspective.